IEEE 802.19.3 Coexistence Recommendations for IEEE 802.11 and IEEE 802.15.4 Based Systems Operating in SUB-1 GHz Frequency Bands - Guo, Jianlin; Nagai, Yukimasa; Rolfe, Benjamin A.; Sumi, Takenori; Orlik, Philip; Robert, Jörg; Yano, Kazuto; Shellhammer, Steve; Kitazawa, Shoichi; Inoue, Yasuhiko; Baykas, Tuncer (IEEE Communications Standards Magazine, 2023)
Internet of Things (IoT) applications are rapidly increasing. A broad range of low-power wide-area technologies have been developed in the Sub-1 GHz frequency bands to meet various application requirements. Massive IEEE 802.15.4g based systems have been deployed to provide low to moderate data rate capabilities. IEEE 802.11ah is designed to provide higher data rate capabilities than the data rates of IEEE 802.15.4g. In addition, other Sub-1 GHz band systems, including LoRa and SigFox, are also installed for applications with longer range communication need. There is considerable overlap in use cases targeted by these technologies. Due to the constrained spectrum allocation in the Sub-1 GHz frequency bands, these systems are likely to coexist. Therefore, the coexistence of heterogeneous Sub-1 GHz band wireless technologies becomes an issue to be addressed. Our measurements and simulations reveal significant interference among these systems. Previously the Sub-1 GHz band coexistence is not well addressed. Accordingly, IEEE New Standards Committee and Standard Board formed IEEE 802.19.3 Task Group in December 2018 to develop IEEE 802.19.3 standard for the coexistence of IEEE 802.11ah and IEEE 802.15.4g based systems to guide product deployment. IEEE 802.19.3 standard was published in April 2021. This article summarizes the Sub-1 GHz band systems, spectrum allocation, interference and noise measurements, coexistence issues, and coexistence recommendations presented in IEEE 802.19.3. It aims to introduce IEEE 802.19.3 standard to readers outside of IEEE 802 standard body and to application developers to raise awareness of potential coexistence issues and available coexistence techniques for the better system deployment. In addition, this article presents performance evaluation of the coexistence methods recommended in IEEE 802.19.3.
CRIS-Team Scopus Importer:2023-07-07